2021
DOI: 10.1016/j.zefq.2021.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on professional practice and patient volume in medical practices: A survey among German physicians and psychotherapists

Abstract: Introduction: This study examines the consequences of the COVID-19 pandemic on outpatient care in the German federal state of Brandenburg during the first 'lockdown' between 22 March and 4 May 2020, focusing on the burden for physicians and psychotherapists in outpatient practices and on alternative ways to provide care, in particular telehealth. Methods: We conducted an online cross-sectional survey among outpatient health care professionals. The responses of n = 277 physicians and n = 87 psychotherapists wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 17 publications
(19 reference statements)
1
17
0
3
Order By: Relevance
“…All data reported in this study were collected shortly before the COVID-19 outbreak. The pandemic, infection control measures, and changes in traditional health care delivery, however, have impacted patient and professional stakeholder perspectives on telemedicine globally [ 45 ], locally [ 25 ], and specifically in rheumatology care as well [ 26 , 46 ], resulting in massive uptake of telemedicine and digital health care. The necessity of using telemedicine to reduce contacts and infection transmission may have led many to their first experiences with telemedicine and might have contributed to the increased acceptance of telemedicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All data reported in this study were collected shortly before the COVID-19 outbreak. The pandemic, infection control measures, and changes in traditional health care delivery, however, have impacted patient and professional stakeholder perspectives on telemedicine globally [ 45 ], locally [ 25 ], and specifically in rheumatology care as well [ 26 , 46 ], resulting in massive uptake of telemedicine and digital health care. The necessity of using telemedicine to reduce contacts and infection transmission may have led many to their first experiences with telemedicine and might have contributed to the increased acceptance of telemedicine.…”
Section: Discussionmentioning
confidence: 99%
“…Shortly after its release, COVID-19 hit health care systems worldwide, leading to dramatic changes in health care delivery. Telemedicine thus became a necessity to reduce the number of contacts and control transmission, leading to an upturn in the use [ 25 ] and acceptance of telemedicine services in Germany [ 21 , 26 ]. This was initially reflected in a massive increase in the volume of telemedicine services billed by medical practices in Germany [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, entrance barriers to the intervention were lowered with the start of the pandemic, and a slightly different subgroup took advantage of the programme. However, a previous study indicated that doctor visits perceived as non-essential were postponed during the lockdown [ 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2, COVID 19) virus upended health care around the world and forever changed how patients converse with and receive care from providers (1,2). Bruch et al (2) reported that physicians and psychologists in Germany had a shift to more positive attitudes toward telehealth because of the COVID 19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2, COVID 19) virus upended health care around the world and forever changed how patients converse with and receive care from providers (1,2). Bruch et al (2) reported that physicians and psychologists in Germany had a shift to more positive attitudes toward telehealth because of the COVID 19 pandemic. Many clinicians quickly learned to use novel platforms to virtually examine and treat their patients with vestibular disorders and modify how they conducted their physical examination (3).…”
Section: Introductionmentioning
confidence: 99%